2011
DOI: 10.1017/s0022149x11000198
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of Dirofilaria immitis, Borrelia burgdorferi, Ehrlichia canis and Anaplasma phagocytophium in dogs in China

Abstract: A survey of the occurrence of Dirofilaria immitis, Borrelia burgdorferi, Ehrlichia canis and Anaplasma phagocytophium in dogs was undertaken in the People's Republic of China between October 2008 and October 2009. A total of 600 blood samples were taken from dogs in four cities in China: 300 in Beijing, 150 in Shenzhen, 30 in Shanghai and 120 in Zhengzhou. All samples were tested for the heartworm antigen and antibodies of canine B. burgdorferi, E. canis and A. phagocytophium by using the canine SNAP® 4Dx® tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…To date there have only been a few studies on vector-borne agents in Chinese dogs [ 7 9 , 24 , 25 ] but our study has confirmed that B. vogeli , B. gibsoni , E. canis, H. canis and T. orientalis or a closely related organism occur in China. The first three agents are very important pathogens of dogs and veterinarians in China should have an increased awareness of the possibility of infections in their canine patients and appropriate diagnostic tests and treatments should be made available.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…To date there have only been a few studies on vector-borne agents in Chinese dogs [ 7 9 , 24 , 25 ] but our study has confirmed that B. vogeli , B. gibsoni , E. canis, H. canis and T. orientalis or a closely related organism occur in China. The first three agents are very important pathogens of dogs and veterinarians in China should have an increased awareness of the possibility of infections in their canine patients and appropriate diagnostic tests and treatments should be made available.…”
Section: Discussionsupporting
confidence: 69%
“…Although Wang and Zhang et al were unsuccessful in identifying E. canis infections in dogs in China using serology and PCR [ 29 , 30 ], other workers have found serological and molecular evidence of infections in the blood of 2 % of dogs in Shenzhen [ 7 9 ] and the organism in R. sanguineus senso lato ticks from dogs in China [ 31 ]. We have now found PCR evidence that E. canis infections are relatively common in Taixing, Jiangsu province.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of D. immitis infection in dogs in these countries varied markedly: 6.9%–20.9% in Korea [7, 13], 0.33%–3.33% in China [15], 3.6%–8.9% in Portugal [2], 34.13% in Greece [6], and 1%–12.5% in the United States [8]. The present study demonstrated that D. immitis infection is endemic in Japan.…”
Section: Resultsmentioning
confidence: 99%
“…In China, seroprevalences of D. immitis were found in Sichuan, Beijing, Shenzhen, Shanghai, and Zhengzhou [5,6]. However, there is no report on dirofilariasis infection in dogs in Shenyang, northeastern China.…”
mentioning
confidence: 99%